Eficiência agronômica de bactérias diazotróficas na cultura da cana-de-açúcar (Saccharum spp.) - Gírio, Lucas Augusto da Silva [UNESP] (2014)
The growing global demand for cleaner fuels has given prominence to Brazil. The Brazilian government has launched programs that encourage sustainable agriculture, which include biological nitrogen fixation, which may totally or partially replace nitrogen fertilization. Moreover, aiming at greater efficiency, have emerged suggesting new research tillage systems, such as presprouted seedlings (MPB). This study is aimed at evaluating: i) the effects of diazotrophic bacteria inoculation on the formation of sugarcane pre-sprouted seedlings (MPB), originating from individual buds; and (ii) the association of nitrogen application with the initial growth of these seedlings in low fertility soils. The first experiment was conducted in a greenhouse for a duration of 50 days. The second included pots in the field for a duration of 180 days. In both experiments, the design utilized randomized blocks; the first with treatments arranged in a 2 x 3 factorial design (with and without inoculation and three quantities of bud reserve) and the second in 2 x 2 x 4 factorial (with and without inoculation, with and without nitrogen evaluated in four seasons: at 45, 90, 135 and 180 days). The inoculant had an effect on the initial phase and reduced the time to produce pre-sprouted seedlings in the greenhouse. In low fertility soil, the inoculant promoted gains in shoot when associated with N doses. There were no gains in root dry matter production in inoculated soils, however, changes were noted in root architecture, with greater growth in root length. The inoculant revealed a positive effect on plant growth